Central metabolic pathways of Aureobasidium pullulans CGMCC1234 for pullulan production. (10th December 2015) - Sheng, Long; Liu, Chang; Tong, Qunyi; Ma, Meihu
Highlights: The central metabolic pathways of A. pullulans included EMP and PPP, but not ED. Pullulan synthesis was inhibited by iodoacetic acid along with the decrease of ATP. DCW raised firstly then declined as iodoacetic acid increased. A few of iodoacetic acid might impel carbon flux flow toward the PPP. Abstract: With the purpose of understanding the metabolic network of Aureobasidium pullulans, the central metabolic pathways were confirmed by the activities of the key enzymes involved in different pathways. The effect of different iodoacetic acid concentrations on pullulan fermentation was also investigated in this paper. The activities of phosphofructokinases and glucose-6-phosphate dehydrogenase existed in A. pullulans CGMCC1234, whereas 2-keto-3-deoxy-6-phosphogluconate aldolase activity was not detected. We proposed that the central metabolic pathways of A. pullulans CGMCC1234 included EMP and PPP, but no ED. Pullulan production declined fast as the iodoacetic acid increased, while cell growth offered upgrade firstly than descending latter tendency. Compared to the control group, the ratio of ATP/ADP of 0.60 mM iodoacetic acid group was lower at different stages of pullulan fermentation. The findings revealed that low concentration of iodoacetic acid might impel carbon flux flow toward the PPP, but reduce the flux of the EMP.